Quantifying the regulatory potential of genetic variants via a hybrid sequence-oriented model with SVEN - Yu Wang; Nan Liang; Ge Gao (Nature Communications)
Abstract Deciphering how noncoding DNA determines gene expression is critical for decoding the functional genome. Understanding the transcription effects of noncoding genetic variants are still major unsolved problems, which is critical for downstream applications in human genetics and precision medicine. Here, we integrate regulatory-specific neural networks and tissue-specific gradient-boosting trees to build SVEN: a hybrid sequence-oriented architecture that can accurately predict tissue-specific gene expression level and quantify the tissue-specific transcriptomic impacts of structural variants across more than 350 tissues and cell lines. We further systematically screen a large-scale structural variants dataset derived from 3622 individuals and clinical structural variants from ClinVar, and provide an overview of transcriptomic impacts of structural variants in population. As a sequence-oriented model, SVEN is also able to predict regulatory effects for small noncoding variants. We expect that SVEN will enable more effective in silico analysis and interpretation of human genome-wide disease-related genetic variants.